Programming Language Enables Creative Visualization. (Computer (00189162), 2009)
The article reports on the creation by Stanford University of Protovis, a programming language for visualization software design which will enable the development of data display applications. Protovis only requires users to have basic programming skills and this is accessible to both Web designers and technically sophisticated engineers. Mozilla Foundation will distribute the technology in its Thunderbird e-mail client.